Effect of Particle Size and Enzyme Load on the Simultaneous Reactions of Lactose Hydrolysis and Transgalactosylation with Glyoxyl-Agarose Immobilized Beta-Galactosidase from Aspergillus Oryzae - Vera-Vera, C (ELSEVIER SCI LTD, 2018)
The simultaneous reactions of lactose hydrolysis and transgalactosylation in the production of galacto-oligosaccharides (GOS) were evaluated with immobilized Aspergillus oryzae beta-galactosidase in glyoxyl-agarose of different particle sizes (fine and macro) and enzyme loads (1, 10 and 30 mg(proiein)/g(support)) to produce biocatalysts subjected to different magnitudes of internal diffusional restrictions. The ratio of initial reaction rates depended on the initial concentration of lactose: at values higher than 800 mM, the ratio of hydrolysis to total reaction rate (r(hydr)/r(total)), which reflects the hydrolytic potential, had values of 16 and 30%, and the ratio of transgalactosylation to total reaction rates (r(transgal)/r(total)), which reflects the transgalactosylation potential, had values of 84 and 70% with the biocatalysts of smaller size and enzyme load, and bigger size and enzyme load, respectively. Results obtained highlight the fact that the biocatalyst should be optimized with regard to its intended use; beta-galactosidase biocatalysts that have been optimized for lactose hydrolysis can be quite inadequate for performing GOS synthesis.